Turbo Product Codes: Applications, Challenges, and Future Directions - Mukhtar, H.; Al-Dweik, A.; Shami, A. (IEEE Communications surveys and tutorials, 2016)
Turbo product codes (TPCs) have been integrated in several practical applications, and hence, they have been considered widely in the literature where the main aim is improving the error performance and/or reducing the computational and implementation complexity. This paper presents a comprehensive survey of the research that focuses on TPCs in terms of encoding, decoding, error performance, and complexity. Moreover, this paper also considers the advantages of integrating TPCs in hybrid automatic repeat request systems where power optimization becomes very efficient and the complexity can be reduced using the unique properties of TPCs such as error self-detection capabilities. Based on the surveyed literature, the pivotal open research issues in TPCs are presented and discussed.